Diaspora, African Union and Sustainable Regional Integration in Africa - Asogwa, Felix; Didiugwu, Ifeanyi (African Journal of Politics and Administrative Studies, 2014)
The role of African Union in the African integration project has remained a topical issue among scholars. Various views have been canvassed on how to strengthen African Union for a more effective regional integration in Africa. This paper examined the central role the African Diasporas can play in repositioning African Union for a sustainable regional integration in Africa. Its analysis of the situation was anchored on the mo-functionalist integration framework and applied essentially the secondary data gathering techniques. Among other recommendations, it suggested for the creation of a pan-African Diaspora Organization.
Keywords: African; Diaspora; Regional integration